KEABSAHAN ALASAN PENOLAKAN REPUBLIK RAKYAT TIONGKOK TERHADAP PUTUSAN PERMANENT COURT ARBITRATION ATAS SENGKETA KLAIM WILAYAH LAUT CINA SELATAN ANTARA PHILIPINA DAN REPUBLIK RAKYAT TIONGKOK BERDASARKAN HUKUM INTERNASIONAL - Fatmawati, Ana; Aprina, Elsa (Faculty of Law, Parahyangan Catholic University, 2019)
This articles shall discuss the arguments made by the People’s Republic of China in rejecting the Permanent Court of Arbitration’s decision made under the UNCLOS 1982 and which should be regarded as final and binding. The main question is whether the arguments put forward are valid according to international public law, especially in light of the UNCLOS and the general principles of international law regulating dispute settlements and territorial claims. A legal audit, a juridical dogmatic approach, shall be utilized here. The author concludes that not one rule or principles of international law seems to support the arguments made by the PRC in rejecting the validity of the Arbitration’s decision.